Pengaruh SPI, SAKD, SAP dan Transparansi terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Purbalingga - Widodo, Nur Aliya; Arofah, Anastasia Anggarkusuma; Maharani, Destin Alfianika (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2025)
This study aims to empirically examine the influence of the Internal Control System (SPI), Regional Financial Accounting System (SAKD), Government Accounting Standards (SAP), and Transparency on the quality of financial statements in the Regional Government of Purbalingga Regency. The problem of the quality of financial statements is still an important issue in regional financial management, because quality financial reports not only function as a form of accountability to the public, but also as a basis for strategic decision-making for local governments. The research method uses a quantitative approach with questionnaire instruments distributed to 61 respondents, consisting of local government officials involved in the process of preparing financial statements and have met the research criteria. Data analysis was carried out using the inner model and outer model approaches, which resulted in an R-square value of 0.743 for the financial report quality variable. This value shows that the independent variables in this study were able to explain 74.3% of the variation in the quality of financial statements, while the rest was influenced by other factors outside the research model. The results of the analysis show that the SAKD and Transparency variables have a significant influence on the quality of local government financial statements. This confirms that a good financial accounting system and transparency in public budget management are the main factors that can improve the reliability, relevance, and accountability of financial statements. On the other hand, the SPI and SAP variables did not have a significant effect, which shows that the implementation of both still needs evaluation and improvement in order to make a real contribution to the quality of financial statements.